Cytoplasmic abnormalities of mature oocytes have a significant effect on fertilization in Bologna poor responders - AKDENİZ, ESRA (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2018)
Background/aim: We aimed to investigate whether oocyte morphologic abnormalities affected cycle outcome in poor responder infertile women who fulfilled the Bologna criteria. Materials and methods: Data were obtained from infertile couples who underwent ICSI and embryo transfer at the Zeynep Kamil Maternity and Children's Health Training and Research Hospital Assisted Reproduction Unit in Istanbul, Turkey. They were allocated to two groups: Group A, poor responders, and Group B, normal responders. All morphological abnormalities of oocytes retrieved were reviewed and grouped as cytoplasmic abnormalities or extracytoplasmic abnormalities. All morphological features were compared between the poor and normal responder groups. ICSI cycle outcomes were described as biochemical pregnancy, fertilization rate, number of top-quality zygotes, top-quality zygote rate, number of embryos transferred, and number of top-quality embryos transferred. The relation between each morphological feature and ICSI outcomes was investigated in each group. Results: The results showed no difference between the groups in terms of morphological features of oocytes. The relation between ICSI cycle outcomes and each oocyte morphological feature was compared in the poor and normal responder groups. Presence of cytoplasmic morphological abnormality was found to significantly correlate with the fertilization rate (P = 0.019) in poor responders. Conclusion: Our data show that oocyte cytoplasmic abnormalities significantly reduce fertilization achievement in poor responders.
Keywords: Fertilization; intracytoplasmic sperm injection; oocyte morphology; poor responder; IN-VITRO FERTILIZATION; MORPHOLOGY; STIMULATION; DEFINITION; INJECTION